The effects of tamarind (Tamarindus indica) and avocado (Persea americana) seeds on lipid and carbohydrate metabolism in rats / Uzukwu Emmanuel Uchenna - Uzukwu Emmanuel, Uchenna (2011)
Tamarind (T) or avocado (A) seed was included in diets offered to rats. Its effects on growth performance, blood glucose and cholesterol levels, and glycogen in liver of rats were studied in three different experiments involving two species of rats (Sprague Dawley (SD) and out bred of Wistar-Kyoto rats-SHR (spontaneously hypertensive rats). Basal diet (BD) and high sucrose diet (HSD) containing ground dried of T or A at the following inclusion 2, 4 or 8% were offered to SD rats in experiments 1 (n=28) and 2 (n=28) respectively, while SHR received BD in experiment 3 (n=28). Feed intake, fecal output and body weight were measured; samples of liver were analyzed for glycogen, whereas serum cholesterol and glucose content were determined. The T inclusion in the diet did not affect the feed intake of SD except for the SHR, where the feed intake was lowered at the highest inclusion of T. The increase in the body weight of the rat in the control and experimental group varied during the trials (p>0.05) with indications of impaired assimilation of nutrient (i.e. reduced feed efficiency) in SHR after extended feeding on the diet containing T. The digestibility of the diet was not affected by T inclusion in the diet offered to the rats. Feed conversion efficiency was better in SD fed with 2%T than in control (12.5±2.8 and 27.1±2.3 respectively; p<0.05) and 4%T in SHR (12.49±2.80) compared to control (0%T; 14.37±1.83; p>0.05). Protein efficiency ratio improved only at 2%T (0.53±0.20) in SD offered BD compared to control (0.19±0.02). The serum cholesterol level of SD offered BD was reduced at all level of T inclusion (2%(0.50±0.17g/l), 4%(0.24±0.14g/l), and 8%(0.31±0.06g/l)) compared to control (0.79±0.04g/l; p<0.05) whereas the serum glucose levels of the SHR (50.74±2.50mg/dl for 4%T) was lower than control (93.52±10.83mg/dl; p<0.05). ii Higher liver glycogen content (8%T; 3.43±0.55mg/g) compared to control (1.27±0.24mg/g; p<0.05) was found only in the SHR group. The rats fed on diets containing avocado seed showed increased intake of feed. There were indications of impaired assimilation of nutrients (i.e. reduced feed efficiency) in SD rats offered HSD when T was added. The digestibility of the diets was not affected at the inclusion of A in the diet offered to the rats. Feed conversion efficiency was better in 2 and 4 %A (16.78± 0.97 and 15.53±1.58 respectively; p<0.05) compared with control (0%A; 27.11±2.28; p<0.05) whereas protein efficiency ratio was better in the SD treated groups than the control. The serum cholesterol level of SD offered BD and SHR were lowered with the inclusion of tamarind seed when compared to control (p<0.05) whereas the addition of avocado seed lowered the glucose levels at 2%A (21.35±2.29mg/dl) for the SD offered BD compared to control (0%T; 41.72±12.46mg/dl; p<0.05). The liver glycogen content increased with the inclusion of avocado seed to the diet of the rats in the treated groups. Tamarind or avocado seed can lower blood glucose and serum cholesterol and also enhance storage of glycogen where included to diet offered to rats. It may also partially influence feed and growth performance though the effect is dose dependent.